Penggunaan dan Penyalahgunaan Kebudayaan di Indonesia: Kebijakan Negara dalam Pemecahan Konflik Etnis - Irwan Abdullah (Antropologi Indonesia, 2001)
The ethnic conflict in Indonesia is a sign of huge problems facing Jakarta and local areas Indonesia, therefore the explanation for its occurrence cannot be produced without examining the central-periphery relations, which involve structural problems in constructing and maintaining power. Ethnicity, for instance, has become political commodity, which is constructed by central powers and made manifest through the concept of SARA (ethnicity, religion, race and inter-group relations). Thus, government tends to find and explain the root of ethnic conflict in ethnic cultural differences itself, whereby differences of ideology and life practices are viewed as the source of conflict. This article attempts to examine ethnic conflict by analyzing three main factors, which are first, the change in the balance of ethnic relations. Second, the imposition of a uniform politics in pluralistic society. Third, a weakening of traditional relationship and the credibility of local elites as a result of government intervention. Based on these three factors, this article concludes that ethnic conflicts are not only matters of ethnic cultural differences, but also are rooted much deeper in systematic mistakes in managing these differences and the conflicts itself ,where culture has been used for government's political interests.